Effective and Ineffective English Teacher - Atmowardoyo, Haryanto; Sakkir, Geminastiti; Sakkir, Rini Isnaeni (Har Press Indonesia, 2024)
This study examines the evolving role of English as a Foreign Language (EFL) teachers in the context of curriculum changes in Indonesia. The research addresses two key objectives: (1) to describe the characteristics of effective English teachers and (2) to identify the traits of ineffective English teachers. As educational reforms in Indonesia prompt shifts in teaching strategies, understanding these characteristics is critical to fostering improved learning outcomes in the EFL classroom. Using a qualitative descriptive research design, this study employs an interpretive approach to gather and analyze data. Qualitative research, in this context, attempts to describe and explain the teaching phenomena as they occur naturally. The study relies on interviews, observations, and document analysis to collect data, which is presented descriptively rather than numerically. The findings highlight the importance of adaptive teaching methods, pedagogical skills, and student-centered learning approaches in shaping the effectiveness of English teachers. Conversely, ineffective teachers tend to lack adaptability, demonstrate poor classroom management, and fail to engage students actively in the learning process. The significance of this research lies in its potential to inform teacher training programs and professional development initiatives. By providing a clear delineation between effective and ineffective teaching practices, the study offers valuable insights into how teachers can better align their methods with contemporary curriculum demands. This, in turn, can lead to enhanced critical thinking and language skills among EFL students in Indonesia. This research contributes to the growing body of literature on EFL teaching in Indonesia and underscores the need for continuous adaptation in teaching methodologies to meet evolving educational standards.